Measurements of the Branching fractions for $B_(s) -> D_(s)πππ$ and $Λ_b^0 -> Λ_c^+πππ$ - Collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Cartelle, P; et al. (2011)
Branching fractions of the decays $H_b→ H_cπ^-π^+π^-$ relative to $H_b→ H_cπ^-$ are presented, where $H_b$ ($H_c$) represents B^0-bar($D^+$), $B^-$ ($D^0$), B_s^0-bar ($D_s^+$) and $Λ_b^0$ ($Λ_c^+$). The measurements are performed with the LHCb detector using 35${\rm pb^{-1}}$ of data collected at $\sqrt{s}=7$ TeV. The ratios of branching fractions are measured to be B(B^0-bar -> D^+π^-π^+π^-)/ B(B^0-bar -> D^+π^-) = 2.38±0.11±0.21 B(B^- -> D^0π^-π^+π^-) / B(B^- -> D^0π^-) = 1.27±0.06±0.11 B(B_s^0-bar -> D_s^+π^-π^+π^-) / B(B_s^0-bar -> D_s^+π^-) = 2.01±0.37±0.20 B(Λ_b^0->Λ_c^+π^-π^+π^-) / B(Λ_b^0 -> Λ_c^+π^-) = 1.43±0.16±0.13. We also report measurements of partial decay rates of these decays to excited charm hadrons. These results are of comparable or higher precision than existing measurements.